Thomas & friends. Blue Mountain mystery [videorecording (DVD)] : the movie - Tieman, Greg; Brandon, Michael, 1945-; Bedella, David, 1962-; Gallagher, Teresa, 1971-; Hope, William, 1955-; Kynman, Steven; Shale, Kerry; Sherman, Martin T.; Awdry, W. (Lionsgate, 2012)
When trouble strikes at the Blue Mountain Quarry, Thomas is sent to help his Narrow Gauge engine friends. While shunting and hauling, he discovers a little green engine hiding in the tunnels. Thomas is determined to get to the bottom of the mystery but discovering the truth is harder than he imagined! Will Thomas be able to help his new friend? or will the little engine be sent away from Sodor forever? Find out in Thomas' most mysterious adventure yet, a movie the whole family will love!